The Economic, Social and Environmental Effects of the Kahramanmaraş Earthquakes: The Case of Elbistan - Nükhet Hotar; Asuman Altay; Çağnur Balsarı; Özlem Çakır; Zeki Atıl Bulut; Üzeyir Aydın; Ceyhun Güler; Yakup Özkaya (Sosyal Siyaset Konferansları Dergisi)
This study aims to compile the economic, social, and environmental impacts of the Kahramanmaraş earthquakes and analyze these impacts with qualitative data, focusing on the Elbistan case. To achieve this goal, data was collected after the earthquakes centered in Kahramanmaraş on February 6, 2023, which affected 11 provinces, to identify the economic, social, and environmental problem areas in Elbistan, the epicenter of the earthquake, and to develop solutions that contribute to regional development. To this end, semi-structured interviews were conducted with key sources of information in Elbistan, including local authorities, district residents, the chambers of commerce, İŞKUR (Turkish Employment Agency), union representatives, industry and university representatives, and local businesses. Qualitative research methods were used in the study, and content analysis was performed. Based on the results obtained through content analysis, policy recommendations have been presented in a structure that aligns with the economic development plans strategy, aimed at restoring or improving the economic, physical, social, cultural, and environmental assets of the affected district, reversing economic decline, and enhancing societal resilience.